2022
DOI: 10.3389/fmicb.2022.858777
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Detection of Bacterial Pathogens and Antimicrobial Resistance Genes in Clinical Urine Samples With Urinary Tract Infection by Metagenomic Nanopore Sequencing

Abstract: Urinary tract infections (UTIs) are among the most common acquired bacterial infections in humans. The current gold standard method for identification of uropathogens in clinical laboratories is cultivation. However, culture-based assays have substantial drawbacks, including long turnaround time and limited culturability of many potential pathogens. Nanopore sequencing technology can overcome these limitations and detect pathogens while also providing reliable predictions of drug susceptibility in clinical sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 55 publications
1
22
0
1
Order By: Relevance
“…Furthermore, our data showed how MinION sequencing could provide extra diagnostic confidence when there is a disagreement between colony morphology and PCR results. Although similar promising results were previously reported for blood (Taxt et al, 2020) and urine (Zhang et al, 2022) specimens, this is the first study that reported how to handle mastitis milk samples for effective and rapid pathogen and AMR detection.…”
Section: Effective Host Cell Depletion and Dna Degradation Improved T...supporting
confidence: 85%
“…Furthermore, our data showed how MinION sequencing could provide extra diagnostic confidence when there is a disagreement between colony morphology and PCR results. Although similar promising results were previously reported for blood (Taxt et al, 2020) and urine (Zhang et al, 2022) specimens, this is the first study that reported how to handle mastitis milk samples for effective and rapid pathogen and AMR detection.…”
Section: Effective Host Cell Depletion and Dna Degradation Improved T...supporting
confidence: 85%
“…The applications of mNGS on non-sterile materials (e.g., urine) remains are still scarce and controversial. In one of the few recent studies on urine (Zhang et al, 2021;Zhang et al, 2022), a prospective proof-ofconcept study by Janes, V. A and colleagues confirmed the feasibility of metagenomic sequencing in detecting of urinary pathogens and drug resistance (Janes et al, 2022). We conducted a mNGS study in patients with suspected UTI and compared it with conventional test in terms of diagnostic performance, pathogenic findings to demonstrate its significance.…”
Section: Discussionmentioning
confidence: 95%
“…In addition, the respective libraries were pooled and multiplex sequencing was performed to improve cost-effectiveness, making the sequencing cost drop to $92. 17 Although the cost for a microbial culture is $60, more than one test and/or combinations with other ones (such as staining, immunology-related tests and/or PCR test) are often needed, the sequencing-based method developed here is more feasible and cost-effective.…”
Section: Discussionmentioning
confidence: 99%
“…13 In contrast, the real-time analysis and ultra-long reads (>100kb)-based approaches, such as the nanopore sequencing is more suitable for clinical laboratories. 14,15 In this regard, the feasibility of the nanopore sequencing application for clinical diagnosis has been demonstrated in clinical cases of meningitis, 16 peritonitis, 12 urinary tract infection, 17 lower respiratory infection, 18 and sepsis. 19 However, due to several combinations of the pathogens isolated in different clinical cases, suitable mNGS approaches for comprehensive pathogens detection and drug resistance prediction of VAP in ICU are still limited.…”
Section: Introductionmentioning
confidence: 99%